tRNAs as regulators of biological processes - Raina, Medha; Ibba, Michael (Frontiers in Genetics, 2014)
Transfer RNAs (tRNA) are best known for their role as adaptors during translation of the genetic code. Beyond their canonical role during protein biosynthesis, tRNAs also perform additional functions in both prokaryotes and eukaryotes for example in regulating gene expression. Aminoacylated tRNAs have also been implicated as substrates for non-ribosomal peptide bond formation, post-translational protein labeling, modification of phospholipids in the cell membrane and antibiotic biosyntheses. Most recently tRNA fragments, or tRFs, have also been recognized to play regulatory roles. Here we examine in more details some of the new functions emerging for tRNA in a variety of cellular processes outside of protein synthesis.